1984
DOI: 10.3109/13813458409071158
|View full text |Cite
|
Sign up to set email alerts
|

The use of low doses of dopamine in intensive care medicine

Abstract: The dopamine alpha- and beta-adrenoceptor dose-response curves are investigated in four patients who are exempt from cardiovascular disease. A dose-related increase in CO, HR and SV is observed with infusion rates of up to 3 micrograms kg-1 min-1. With concentrations greater than 10 micrograms kg-1 min-1, both BP and SVR increase. Low-dose dopamine infusion less than 3 micrograms kg-1 min-1 is investigated in ten other patients. With this infusion rate, a selective renal vasodilation is induced without periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…These findings support previous reports indicating that the dose of dopamine that produces the maximal increase in RBF in patients with HF is higher than the dose commonly thought of as the low "renal" dose. 12,24,25 The present results reflect the known pharmacology of dopamine, which has been shown to exhibit a graded pharmacological response, with a dose-dependent predominant activation of dopaminergic receptors, ␤-receptors, and ␣-receptors. 11,26 Generally, at doses Ͻ3 g · kg Ϫ1 · min Ϫ1 , dopamine has been found to activate dopamine A1 receptors, which cause vasodilation of the renal arteries and other vascular beds, including mesenteric, coronary, and cerebral beds.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These findings support previous reports indicating that the dose of dopamine that produces the maximal increase in RBF in patients with HF is higher than the dose commonly thought of as the low "renal" dose. 12,24,25 The present results reflect the known pharmacology of dopamine, which has been shown to exhibit a graded pharmacological response, with a dose-dependent predominant activation of dopaminergic receptors, ␤-receptors, and ␣-receptors. 11,26 Generally, at doses Ͻ3 g · kg Ϫ1 · min Ϫ1 , dopamine has been found to activate dopamine A1 receptors, which cause vasodilation of the renal arteries and other vascular beds, including mesenteric, coronary, and cerebral beds.…”
Section: Discussionmentioning
confidence: 56%
“…6 -10 Dopamine has been reported both in experimental animals and in a variety of patient populations to enhance RBF by multiple mechanisms, including an increase in CO and local vasodilation due to stimulation of dopamine receptors in renal blood vessels. 11 For many years, a small dose of dopamine often has been used by clinicians to enhance RBF in critically ill patients 12,13 ; however, this selective effect of dopamine on the renal circulation may be eliminated or markedly attenuated by other vasoconstrictive mechanisms known to be activated in patients with HF. 14 In addition, the magnitude of its renal vasodilatory effects and site of action in patients with HF have not been clearly defined.…”
Section: Clinical Perspective P 205mentioning
confidence: 99%
“…20 These authors found that the activity of this agent on β1 receptors was reflected in improved cardiac output, while stimulation of α1 receptors led to increased systemic arterial pressure. They furthermore concluded that, at doses equal to or smaller than 2 µg/kg/min, dopamine has selective action on the dopaminergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Since dopamine was first synthesized in 1910, a large amount of research related to this drug has allowed identification of its effects and mechanism of action, 2,8,20 and also definition of its therapeutic possibilities. The idea that LDD could prevent acute renal failure arose naturally from knowledge of its selective renal vasodilatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…At this time plasma dopamine concentrations are about ten-fold higher than baseline and plasma L-dopa concentrations are approaching 1 ,umol 1-1. The effects of low dose infusions of dopamine on blood pressure in normal man have been reported as causing no change (Levinson et al, 1985) or a small fall (d'Orio et al, 1984). L-dopa causes hypotension in dogs (Reid et al, 1986) and in Parkinsonian (Calne et al, 1970) and hypertensive patients but not normal man (Saito et al, 1987;Ansel & Markham 1970).…”
Section: Adverse Reactions To Gludopamentioning
confidence: 99%